Atrial fibrillation in heart failure: a comprehensive review - Deedwania, Prakash C; Lardizabal, Joel A (The American journal of medicine, 2010)
Chronic heart failure and atrial fibrillation are 2 major disorders that are closely linked. Their coexistence is associated with adverse prognosis. Both share several common predisposing conditions, but their interaction involves complex ultrastructural, electrophysiologic, and neurohormonal processes that go beyond mere sharing of mutual risk factors. Rate control approach remains the standard therapy for atrial fibrillation in heart failure because current strategies at rhythm control have so far failed to positively impact mortality and morbidity. This is largely because of the shortcomings of current pharmacologic anti-arrhythmic agents. Surgical and catheter-based therapies are promising, but long-term data are lacking. The role of non-anti-arrhythmic therapeutic agents also is being explored. Further progress toward improved understanding the complex relationship between atrial fibrillation and heart failure should improve management strategies.